Osmanthus Fragran Leaves Extract as Corrosion Inhibitor for Carbon Steel in Hydrochloric Acid Solution - Li, L.J.; Zhang, X.P.; Lei, J.L.; He, J.X.; Zhang1, S.T.; Pan, F.S. (Asian Journal of Chemistry, 2011)
The aqueous extract of osmanthus fragran leaves was evaluated as a corrosion inhibitor for carbon steel in 1M hydrochloric acid using electrochemical polarization and electrochemical impedance spectroscopy techniques. The extract was found to reduce the corrosion rate of carbon steel. The inhibition efficiency increased with increasing the extract concentration to exceed 90 % at 0.2040 g/L at 298 K. The inhibition efficiency was temperature independent within 288- 318 K. The extract acted as a mixed inhibitor and did not modify the apparent activation energy of the corrosion process of carbon steel. The adsorption of the extract components on the carbon steel surface belonged to the physical adsorption, which followed Langmuir adsorption isotherm.